The Role of Italy in the Opening and Subsidy of Italian Schools in Albania Before and After April, 1939 - Sota, Jani; Puka, Edi (Richtmann Publishing, 2011)
This article is dedicated to the role of Italy in the opening and support of Italian schools before and after April 1939. Inaddition, the great contribute of Italian teachers in the education field and their efforts in the opening of elementary and general orprofiled high schools for the Albanian students will be treated in this article. Despite the political and propaganda character of theseschools which were subsidized by Italy, they served to the Albanian national inspiration, which from the education, emancipation andnational awareness of the Albanian people gave them a chance to take up and implement the western culture. Sensitivity of the Albanianschool towards the new ideas of western schools would become the main stone of improvement in education and the Albanian school ingeneral. They were represented through activities and achievements of the school towards the new pedagogic ideas and the improvement ofwestern schools and the tendency to represent them in our conditions were supported by the senior executives of education and wereembodied into laws, with educational programs, texts and with serious pedagogical publishing of the time.